Self-perceived preparedness of junior doctors for internship in regional far North Queensland - Sellars, James N.; Mark, Michael van der; Neal, Joanna; Palesy, Tom; Palesy, Lani; Jeyarajan, Eshwarshanker (International Surgery Journal, 2024)
Background: Objective of the study was to determine the self-perceived preparedness and concerns of newly graduated junior doctors beginning their internship year in a regional based hospital in far North Queensland. Methods: A questionnaire investigating the basic demographics, future vocational intentions, perceived medical strengths, and greatest hopes and fears for the upcoming intern year was formulated. The survey was undertaken by all interns starting work in 2023 at Cairns Hospital in regional Far North Queensland. Basic statistical analysis was conducted in Microsoft Excel. Results: There were 52 total participants. Overall, 40 (76.9%) were aged 23 to 32 years, 45 (86.5%) had graduated from a Queensland university, and 25 (48.1%) had previous exposure to the medical field prior to internship, through a family member or previous work. New interns felt least prepared for discussions regarding dying and palliative care, N=14 (26.9%) at least “prepared”, certification of death, N=11 (21.2%) at least “prepared” and nasogastric tube insertion, N=14 (26.9%) at least “prepared”. The main concerns were feeling unsupported (N=31, 59.6%), tiredness and stress (N=28, 53.8%), and interacting with rude staff or experiencing bullying (N=27, 51.9%). Overall, interns felt least prepared for surgical (N=21, 40.4%) and after-hours rotations (N=19, 36.5%). Conclusions: The intern year can be daunting for recent graduates, particularly feeling a sense of isolation and fatigue, heightened by potential staff conflict and high-pressure settings in surgery and after-hours. Better preparation and support should be provided for interns to ensure a comfortable transition from university to work to optimise safe and effective patient care.